PRAGMATICS IN LINGUISTICS: AN EXPLORATION OF CONTEXTUAL MEANING - Raxmonov Timur Ag’zam o’g’li (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: This article examines pragmatics as a significant field of linguistics that studies how meaning is shaped by context in real-life communication. It outlines the key concepts of pragmatic theory, including deixis, speech acts, implicature, presupposition, and the Cooperative Principle. The article highlights the role of social, cultural, and situational factors in interpreting utterances and demonstrates the importance of pragmatic competence in effective communication. It concludes that pragmatics is essential for language learning, intercultural interaction, and discourse analysis, as it reveals how meaning is dynamically constructed through context rather than solely through linguistic structure.